Affects of organizational justice on organizational commitment in terms of survivor syndrome - Yöney, Derya (My University, 2010)
Son finansal krizin tüm dünya üzerinde büyük etkileri olmustur. Bu kriz toplum ekonomilerini yeniden yapılandırmaktadır. Global ekonomik kriz küçülen firmaların is gücünde azalmaya gitmesine neden olmustur. Bir çok isçi issiz bırakılmıstır. slerinin kaybı issiz kalan insanları derinden etkilemistir. Ancak aynı zamanda küçülme sonrası isyerinde çalısmaya devam edenler -geride kalanlar da- isten çıkarmalardan zarar görmüstür. Bu negatif etkiler örgütsel verimliligi de negatif yönde etkilemektedir. Geride kalanların örgüte karsı tutum ve davranısları degismektedir. Çalısanların örgüte baglılıkları ve adalet algıları etkilenmektedir. Bu çalısmanın amacı geride kalanların örgütsel baglılıklarının örgütsel adalet algılarından nasıl etkilendigini arastırmaktır. Hissedilen geride kalanlar sendromunun (yüksek veya düsükse) örgütsel adalet degerleri (dagıtımsal, islemsel, etkilesim) üzerine katkısı bulunmaktadır. Aralarındaki farklılıklar geride kalanların örgütlerine baglılık sekillerini degistirebilmektedir. Örnegin, bazen örgüte duygusal baglılıgı görürken bazen sürekli baglılıgı ve bazen de normatif baglılıgı görebilmekteyiz. Bu çalısmamızda geride kalanlar sendromunun örgütsel adalet üzerindeki katkısının örgütsel baglılıgı etkilemesi bakımından inceledik

The last financial crisis has a big impact all over the world. This crisis restructures the economy on society. Global economic crisis has forced downsized companies to make deep cuts to their work forces. Some of the employees made redundant. The loss of their jobs affected deeply unemployed people. However, at the same time survivors are damaged because of the layoffs too. The socio-psychological impact of downsizing on layoff survivors caused negative impacts on survivors wellbeing and mental-health’s. These negative impacts may negatively influence organizational productivity and changes survivors work attitudes and behaviors toward the organization. Employees work attitudes and behaviors such as commitment to organization and justice perceptions are affected. The aim of this study is to investigate how the survivors’ organizational commitments are affected by their organizational justice perceptions. Perceived survivor syndrome (low or high) has contribution on organizational justice values (distributive, procedural and interactional). Therefore, the differences between perceived justice changes survivors commitment form to the organization. For example, sometimes we can see affective commitment to the organization, sometimes continuance commitment, sometimes-normative commitment. In this study, we examined the contribution of survivor syndrome on justice perceptions that affect organizational commitment.
Keywords: Ekonomik Kriz; Finansal Kriz; Global Kriz